(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the effects of musical stimuli on university performance through heart rate and Rate of Perceived Exertion as a function of a running protocol in deep water. The sample consisted of 18 women aged between 18 and 30 years (23.44 ± 3.42) from Mossoró/RN. Participants were assessed on two separate days, one day with musical stimulation and the other without the stimulus. At the end of each stage reached within the test, the Heart Rate and Rate of Perceived Exertion of each participant were measured before the beginning of the next stage. To compare the performance variables with and without musical stimuli, the paired “t” test. p<0.05. The results showed that they do not present relevant differences in Heart Rate and Rate of Perceived Exertion with and without music, except in stage 1 (p=0.045) and stage 3 (p=0.048) for Heart Rate. It is concluded that the use of music as a stimulus in the performance of university students through a running protocol in a deep pool is a valid strategy for reaching maximum effort or continuity at a moderate/high intensity in the aquatic environment.